The father’s decision making in home birth - Martínez-Mollá, Teresa; Solano Ruiz, Carmen; Siles González, José; Sánchez-Peralvo, Marta; Méndez-Pérez, Gemma (Investigación y Educación en Enfermería, 2015)
Objective. This work sought to inquire on the father’s role on the decision making regarding home birth from the perspective of both partners. Methodology. The design was ethnographic of qualitative nature, conducted in the province of Alicante, Spain. A total of 11 couples participated voluntarily in the study. To gather the data, the following techniques were used: two life stories, five narrations, and in-depth interviews of all the study participants. The data obtained were analyzed with the ATLAS-ti v6.2 software. Results. Four fundamental categories were obtained: father’s attitude, role performed, influencing factors, and perception of the woman. The proposal to carry out the delivery at home tends to be made by the woman, but its decision is made jointly. This decision is influenced by different factors, like: good evolution of the pregnancy, accompaniment by a professional, and the couple’s beliefs on the delivery. The fathers consider they must be respectful of the woman’s decision and accompany them during the whole process; the women are comforted by their unconditional support and accompaniment, considering it essential. Conclusion. The father’s role is fundamental in the planned decision of having a home birth; a decision discussed and mediated by the couple in which their fears and beliefs are determinant in their decision. The woman has her partner’s support to implement her decision. How to cite this article: Martínez-Mollá T, Solano C, Siles J, Sánchez-Peralvo M, Méndez-Pérez G. The father’s decision making in home birth. Invest Educ Enferm. 2015; 33(3):